Formal Methods and Software Engineering : 18th International Conference on Formal Engineering Methods, ICFEM 2016, Tokyo, Japan, November 14-18, 2016, Proceedings /: 18th International Conference on Formal Engineering Methods, ICFEM 2016, Tokyo, Japan, November 14-18, 2016, Proceedings. (2016) - Unknown
No abstract available